IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 24 TAHUN 2018 TENTANG PELAYANAN PERIZINAN BERUSAHA TERINTEGRASI SECARA ELEKTRONIK PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN PONOROGO - Nugroho, Ahmad Sholeh (Master of Public Administration, Universitas Slamet Riyadi, 2021)
In the context of accelerating and increasing investment and business, a Government Regulation Number 24 of 2018 concerning Business Licensing Services is Integrated Electronically. Based on this policy, all business licensing services become integrated by the center through one system, Online Single Submission (OSS). OSS is a licensing service system that aims to simplify business licensing and create a model of integrated licensing services that is fast, inexpensive and provides certainty. Ponorogo Regency's One-Stop Integrated Service and Investment Service (DPMPTSP) is one of the regional government apparatus in Ponorogo Regency that implements a one-stop service system as a service agency that is specifically tasked with providing licensing services that directly intersect with the community, one of which is Business Licensing Services through OSS.The purpose of this study is to describe in depth and analyze the Implementation of Online Single Submission (OSS) Integrated Business Licensing Services in Ponorogo Regency DPMPTSP. This type of research is descriptive with a qualitative approach.The results of the Integrated Electronic Business Licensing Services Implementation Online Single Submission (OSS) at Ponorogo Regency DPMPTSP have been implemented, but there are still obstacles in the delivery of information that is not fully acceptable to the community.The use of a business licensing system through OSS resulted in the community still does not understand the procedures for managing a business.Ponorogo people as potential individuals who went directly to DPMPTSP Ponorogo Regency in managing business permits. Human resources at the service level are sufficient in their implementation. Supporting facilities for the implementation of licensing services through OSS in Ponorogo Regency DPMPTSP are quite good, which consists of computers, printers and internet networks. In the aspect of disposition, the appointment of bureaucracy is carried out based on the letter of assignment of the Head of Service.There was no incentive obtained by the executor of the OSS Business Licensing Service in Ponorogo Regency DPMPTSP.The bureaucratic structure has been carried out in accordance with the main tasks and functions that exist. Through OSS services, the benefits provided, namely DPMPTSP, can easily access licensing, trying to directly complete one day.